Seed dormancy in ornamental plants: A review - TIWARI, A K; TIWARI, T N; PRASAD, S R (The Indian Journal of Agricultural Sciences, 2016)
Seed is the first input used in transfer of genetic traits in ornamental plants production. Seed dormancy is a physiological phenomenon in plants, which is caused by external or internal factors, and prevents seed germination, even in optimal conditions. Seed dormancy in flower crops impacts both seed production and germination. It can also complicate assessment of seed quality by the seed analyst who requires prompt germination to evaluate a seed lot. Flower crops display diverse mechanisms for seed dormancy like hard seed coat, immature, rudimentary embryo and inhibitors. It can be broken by soil melting and freezing, microorganism’s activity, forest fires, soil activity and being eaten by animals, in normal conditions. This review surveys and categorizes the different seed dormancy conditions found in flowering plants. Flower genera are listed according to dormancy type. Categories of dormancy include primary and secondary dormancy. Within primary dormancy, examples of flower genera can be found that display exogenous, endogenous and combinational dormancy. Secondary dormancy can be an important problem in selected flower seeds. Specific examples are given for each type of dormancy along with methods to alleviate dormancy.